Habilidades sociales y comportamiento prosocial de los estudiantes de la Institución Educativa Primaria N° 60078 Yraida Rojas Regra, distrito de Pebas 2024 - Vasquez Ruiz, Teddy (2025)
The present study aimed to establish the relationship between social skills and prosocial behavior among students of Primary School N° 60078 Yraida Rojas Regra, located in the District of Pebas, during the year 2024. The research followed a quantitative approach, employing a non-experimental, cross-sectional, field based, bivariate, and relational design. The population consisted of 363 students, from which a representative sample of 110 participants was selected. Standardized instruments, such as surveys and questionnaires, were applied to gather the necessary data. The statistical analysis revealed a significant relationship between social skills and prosocial behavior, confirmed through inferential tests. The Spearman’s rho correlation coefficient reached a value of .723, with a p-value of .000, which led to the rejection of the null hypothesis and the confirmation of a positive and strong relationship between both variables. These findings suggest that students with higher social skills are more likely to exhibit favorable prosocial attitudes. This is particularly relevant for strengthening pedagogical strategies aimed at promoting harmonious school coexistence and the integral development of students.